The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/shk.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Role of Elevated Fibrinogen in Burn-Induced Mitochondrial Dysfunction

Abstract: Introduction Skeletal muscle wasting and weakness with mitochondrial dysfunction (MD) are major pathological problems in burn injury (BI) patients. Fibrinogen levels elevated in plasma is an accepted risk factor for poor prognosis in many human diseases, and is also designated one of damage-associated molecular pattern (DAMPs) protein. The roles of upregulated fibrinogen on muscle changes of critical illness including BI are unknown. The hypothesis tested was that BI-upregulated fibrinogen plays a pivotal role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A recent study from Ueki’s report showed elevated fibrinogen levels in plasma-related muscle wasting in burn mice. They confirmed that fibrinogen increased cytokine TNF and chemokine MCP-1 to further damage mitochondria in myotubes (34). Without mentioning the effect of IL-6, the authors conveyed the complexity of cytokine in triggering mitochondrial disturbances and its effect on muscle homeostasis after burn.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study from Ueki’s report showed elevated fibrinogen levels in plasma-related muscle wasting in burn mice. They confirmed that fibrinogen increased cytokine TNF and chemokine MCP-1 to further damage mitochondria in myotubes (34). Without mentioning the effect of IL-6, the authors conveyed the complexity of cytokine in triggering mitochondrial disturbances and its effect on muscle homeostasis after burn.…”
Section: Discussionmentioning
confidence: 73%
“…Burn injury causes mitochondrial dysfunction 2 4 . Next, we studied the effects of FTI on mitochondrial dysfunction in mouse skeletal muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrinogen, as a pro-inflammatory protein commonly involved in the process of hemostasis, has played an important role in both inflammatory responses and tumor progression and metastasis [ 6 8 ]. Numerous studies have reported that fibrinogen level in plasma was upregulated in several types of cancers and related to cancer progression and prognosis [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%